The effects of CuO and SiO2 on aluminum AA6061 hybrid nanocomposite as reinforcements: a concise review - Msebawi, Muntadher Sabah; Leman, Zulkiflle; Shamsudin, Shazarel; Mohd Tahir, Suraya; Jaafar, Che Nor Aiza; Mohamed Ariff, Azmah Hanim; Zahari, Nur Ismarrubie; Rady, Mohammed H. (MDPI AG, 2021)
Hybrid composites are obtained by embedding multiple micro and nano reinforcements into the matrix materials. These hybrid composites are helpful to obtain the useful properties of matrix and reinforcement materials. Aluminum matrix is one the most common matrix materials due to its excellent thermal and electrical properties. This review covers various aspects of nanoparticle-reinforced Al hybrid composites. Solid-state recycling of Al only consumes around 5% of the energy utilized in the conventional extraction and recycling methods. This review revolves around the induction of silica and copper oxide nanoparticles into the solid-state recycled Al matrix material to form the hybrid composite. These nanoparticles enhance stiffness, toughness, and high temperature stability for Al hybrid composites. A detailed analysis was carried out for AA6061-grade Al matrix materials along with the silica and copper oxide nanoparticles. The present work focused on the effects of nano silica and nano copper oxide particle reinforcements on Al-based composite manufactured via hot extrusion process. The composite fabrication through solid-state recycling is discussed in detail. A detailed analysis for the effects of volume fraction and wt.% of CuO and SiO2 reinforcement particles was carried out by various characterization techniques. A detailed comparison in terms of mechanical performance of Al-based composites with the addition of nano silica and nano copper oxide particles is presented here to investigate the efficiency and performance of these particles.